МОЛЕКУЛЯРНО-БИОЛОГИЧЕСКИE МЕТОДЫ В ОЦЕНКЕ МИКРОБНОГО РАЗНООБРАЗИЯ ПОЧВ (Experimental biology, 2015)
There are various methods for assessing of the microbiocenosis structure. Until recently, the microbiological and biochemical methods were primary. However not all soil microorganisms can be revealed by these methods. Nowadays molecular-based techniques are widely applied for theanalysis of microbic populations. In paper the most widespread molecular approaches for studying of soil microbial biota are described. Results of various researches of assessing microbial diversity in the soils using methods of molecular biology are shown. The opportunities of using these methods for microbial communities’ structure and composition analysis, establishment of phylogenetic relations, and also for revealing of the microorganisms which perform the functional role in ecosystems are shown.
Keywords: microbiocenosis; microorganisms